O professor alfabetizador em formação: saberes necessários ao exercício da sua profissão - Fonseca, Luciana Franceschini (2011)
The aim of this study was to investigate the necessary knowledge for the practice of the literacy teacher in professional development, according to theoretical references of authors who are dedicated to the study of teachers education, as Imbernón, Marcelo and Placco; authors who are dedicated to the study of literacy processes, such as Ferreiro, Freire and Soares; and one who is dedicated to the study of teacher s knowledge, as Tardif. An empirical research was carried out, in a qualitative way, as well as procedures for data collection, semi-structured interviews and observation techniques were used and examined from the perspective of theory developed on the theme. The semi-structured interview was conducted by a teacher who was responsible for the phase of school literacy, including the first years of Ensino Fundamental da Educação Básica at a private school in São Paulo City. The observation took place in that specific classroom for two months, through visits and were reported in a field diary. Initially, data analysis was performed, according to several indicators and elaboration of corresponding categories which, analyzed from the perspective of the theory about the topic, led, subsequently, to the discussion on the knowledge used by literacy teachers in their professional function. The conclusion of this study reveals the complex nature of teachers knowledge, since they explicit the close relationship between the knowledge of different natures, arising from the personal, educational, training, disciplinary, curricular, and experiential dimensions, as they are, in many circumstances, complementary. This way, the achieved results provide contributions to the improvement of procedures for training engaged teachers in school teaching, as they provide to the literacy teacher, a design of specific knowledge of their profession, so that the process of literacy can happen satisfactorily, finally benefiting students education